The Determinants of Escape Clause Petitions - Coughlin, Cletus C.; Terza, Joseph V.; Khalifah, Noor Aini (The Review of Economics and Statistics, 1989)
Based on the decision to file an escape clause petition by a firm, a Poisson regression model of the macroeconomic determinants of the total number of these petitions yearly is developed and estimated. The Poisson specification conforms to the fact that the number of escape clause petitions is a non-negative integer with a skewed probability distribution. In addition, the number of potential petitioners is controlled for in the specification. The empirical results suggest that both domestic and international factors affect the decision to file an escape clause petition. The legal environment is found to be a determinant as well. Copyright 1989 by MIT Press.